ANALYSIS THE EFFECTIVENESS OF CIRCUIT TRAINING METHOD ON ENDURANCE ABILITY OF FOOTBALL PLAYERS - Yogi, Ananda Yogi Saputra; Adi s, Adi s (Universitas Negeri Semarang, 2024)
The reason of this inquire about is to see into the utilize Analysis Of Inclusive In circuit training for endurance football players.The PRISMA guidelines for precise audits and meta-analyses were taken after in this audit examination. The consider must be distributed inside the earlier five a long time, from January 2020 to July 2024. Within the look strategy, the taking after watchwords are utilized:(1) circuit training (2) Endurance (3) Football. The search engines Scopus (a large, multidisciplinary database of peer-reviewed literature: scientific journals, books, and conference proceedings). The topic of this inquire about as a entire gotten 358. Contains 309 articles which are at that point taken 10 significant articles. Analysis of circuit training exercises in increasing the endurance of soccer players in this study obtained data in Scopus and then processed it into a research analysis with the topic circuit training, endurance, and soccer with a total of 358 search results and 309 articles with the right topic and 10 articles taken as material for the analysis of this research.